Pottery technology in the Tang dynasty (ninth century ad): archaeometric analyses of a Gongyi sherd found at Siraf, Iran. (18th December 2018) - Spataro, M.; Wood, N.; Meeks, N.; Meek, A.; Priestman, S.
Abstract : In 1969–70, a single Tang dynasty blue‐spotted Gongyi sherd was found at Siraf, Iran, the main trading port on the Persian Gulf in the early Islamic period. This is the only known example of Chinese blue‐and‐white ware, whether low‐ or high‐fired, found in the Middle East from such an early date. The sherd provides direct archaeological evidence for the Indian Ocean trade between China and the Middle East in the ninth centuryad . The body paste, clear glaze and blue glaze or pigment were analysed by thin‐section petrography, scanning electron microscopy with energy‐dispersive X‐ray spectrometry (SEM‐EDX) and X‐ray fluorescence (XRF). The technological analysis reveals the different steps of the chaîne opératoire : clay mixing, slip and glaze application, and decoration with the cobalt blue glaze before high‐temperature firing. These steps are characteristic of Tang stoneware production at Gongyi in Henan province, China. The use of cobalt blue pigment as part of a simple spotted decoration scheme on the Gongyi sherd, and its find context within the Middle East, provides evidence for the complex interplay and influence occurring between Chinese and Middle East ceramic industries at this time. Closely comparable examples of contemporary low‐fired earthenware ceramics with cobalt blue decoration on a white tin glaze manufactured within the Middle East also occur within the same assemblage from Siraf.